Familial aggregation in developmental topographical disorientation (DTD). Issue 7 (16th November 2016) - Barclay, Sarah F.; Burles, Ford; Potocki, Kendra; Rancourt, Kate M.; Nicolson, Mary Lou; Bech-Hansen, N. Torben; Iaria, Giuseppe
ABSTRACT: A variety of brain lesions may affect the ability to orient, resulting in what is termed "acquired topographical disorientation". In some individuals, however, topographical disorientation is present from childhood, with no apparent brain abnormalities and otherwise intact general cognitive abilities, a condition referred to as "developmental topographical disorientation" (DTD). Individuals affected by DTD often report relatives experiencing the same lifelong orientation difficulties. Here, we sought to assess the familial aggregation of DTD by investigating its occurrence in the families of DTD probands, and in the families of control probands who did not experience topographical disorientation. We found that DTD appears to cluster in the DTD families, with tested relatives displaying the trait, whereas in the control families we did not detect any individuals with DTD. These findings provide the very first evidence for the familial clustering of DTD and motivate further work investigating the genetic factors producing this clustering.